Assessment of sludge formation in diesel storage tanks and eradication measures. Issue 1 (September 2021) - Kumar, Priyal; Durga Pradeep Raavi, L K; Kumar, Ashwin Anil; Dumpala, Ravikumar
Abstract: The sludge formation and its accumulation in fuel tanks cause several problems such as clogging of vent and suction pipes, reduction in fuel quality and tank capacity, and deterioration of tank material. Sludge is a complex composition of water, fuel, sand, waste oil, metals, bacteria, minerals, and other organic matter. It grows with time because of bacterial growth (that feeds on fuel and water), impurities, and the aerobic polymerization of hydrocarbons in the fuel. The main objective of the present work is to delay the sludge from forming in the diesel storage tanks. It aims at breaking down information collected from various sources on how sludge formation occurs with time and produce research results on the chemical analysis performed on a diesel sludge sample collected from a fuel depot. Two experimental cases have been set up to show how stirring affects sludge growth over a period of time. It is observed that the sludge growth is less in the sample that is agitated when compared with the sample without agitation. By taking this into account, a stirring design isproposed and developed. Also, an idea is provided for reducing the metal ions in the sludge, thus maintaining a high-quality fuel ready for dispensing at the fuel stations.